Reflexion und Reflexivität in Unterricht, Schule und Lehrer:innenbildung - Reintjes, Christian; Kunze, Ingrid (Studien zur Professionsforschung und Lehrer:innenbildung, 2022)
Currently, the call for an increase in the 'reflective ability' of teachers in the course of school and lesson development, of students in the course of the expectation of shaping their own learning and educational path, and of student teachers and trainee teachers in the course of their professionalization is getting louder. The resulting current challenges in education were discussed at a conference of the DGfE Section School Education in the fall of 2021 at the University of Osnabrück. This edited volume brings together contributions that emerged from selected symposia and open up diverse perspectives on the paradigm of reflection. In a first part, the theoretical discourses on reflection and reflexivity are deepened. This is followed by essays that focus the perspective on reflection and reflexivity in teacher education and examine the topic in relation to schools and teaching. The series "Studies on Professional Research and Teacher Education" is edited by Manuela Keller-Schneider, Katharina Kunze, Tobias Leonhard and Christian Reintjes.